Semi-formal Islamic microfinance institutions in Nigeria: the experience of Al-Hayat relief foundation - Salako, Taofiki (Universiti Pendidikan Sultan Idris, 2018)
Semi-formal Islamic microfinance institutions in Nigeria: the experience of Al-Hayat relief foundation by Salako, Taofiki